2006
DOI: 10.1093/humrep/del354
|View full text |Cite
|
Sign up to set email alerts
|

Successful delivery after the transfer of twice-vitrified embryos derived from in vitro matured oocytes: A Case Report

Abstract: We report here the first case of successful pregnancy and delivery after the blastocyst transfer of twice-vitrified embryos produced following in vitro maturation (IVM) and ICSI. The patient received 5000 IU hCG on day 12 of the treatment cycle, and oocyte retrieval was carried out 36 h after hCG injection. A total of 22 immature oocytes were obtained. Following incubation for 26 h in IVM medium, 15 oocytes (68.2%) reached metaphase II stage. In total, 13 oocytes (86.7%) were fertilized after ICSI with the hus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 17 publications
1
15
0
4
Order By: Relevance
“…This way, many embryos are wasted after the transfer of the best ones in a cryopreseved cycle, which could either be used in further cycles or donated to research. Our case corroborates previous finding [5] and emphasizes the pregnancy potential of vitrified blastocysts generated after in vitro culture of frozen/thawed cleavage stage embryos.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This way, many embryos are wasted after the transfer of the best ones in a cryopreseved cycle, which could either be used in further cycles or donated to research. Our case corroborates previous finding [5] and emphasizes the pregnancy potential of vitrified blastocysts generated after in vitro culture of frozen/thawed cleavage stage embryos.…”
Section: Discussionsupporting
confidence: 92%
“…It has already been reported that human embryos twice frozen or vitrified can result in successful deliveries ( [4,5]). Moreover, one case report describes the birth of twins after the transfer of 2 vitrified-rewarmed blastocysts generated from frozen cleavage stage embryos [6].…”
Section: Introductionmentioning
confidence: 99%
“…Blastocysts that were scored at least 3AA without C by Gardner's criteria were vitrified as good blastocyst. The endometrium was prepared using methodology described previously [9], modified by administration of GnRH agonist (600 μg/day, Suprecur® nasal solution 0.15 %; Mochida Pharmaceutical, Tokyo, Japan) for 3 weeks followed by incremental doses of oral oestradiol valerate (Progynova®; Bayer Schering Pharma, Zürich, Switzerland) from 1 to 4 mg for 2 weeks. After using ultrasonography to confirm the endometrial thickness to be more than 8 mm, 6 mg/day chlormadinone acetate (Lutoral®; Shionogi & Co., Osaka, Japan) was administered.. Progesterone (Progeston depot® 125 mg; Fuji Pharma Co., Toyama, Japan) was administered intramuscularly on the day of embryo transfer, with two additional doses after conception.…”
Section: Study 3: Implantation Competence After Embryo Transfermentioning
confidence: 99%
“…Conversely, only limited published data are available for FET with human embryos that were frozen-thawed twice (6,7). To our knowledge, the description of successful live births derived from refrozen embryos is limited to case reports (8)(9)(10)(11)(12)(13)(14)(15)(16); therefore, we retrospectively analyzed our clinical data on refrozen-thawed ETs, including perinatal outcomes of children born after embryo re-cryopreservation, to evaluate the safety of the refreezing procedure.…”
mentioning
confidence: 99%